Perlindungan Hukum Bagi Konsumen Dalam Transaksi Jual Beli-Online (E-Commerce) - Hendryan, Dery; Ganiarta, Leonardo; Aryani, Gustina (Universitas Sang Bumi Ruwa Jurai, 2024)
Advances in technology and the internet have caused many negative things for the users. To do business and transaction on the internet need an understanding, seriousness and a desire. In an agreement, one of the parties/parties often has to face difficult conditions and, in the end, the agreed contact/agreement cannot work/be carried out as well as it should. The factors that cause difficult events can occur intentionally or unintentionally. Breach of contract is a condition/situation that can be committed by one of the parties or parties in an agreement, that is, in general it can be described as that the contents of the agreement are not carried out properly and are not in accordance with what was agreed upon from the start. Plunging directly into the business of buying and selling online/transacting electronically (e-commerce) is an action that is rarely done but has become a lifestyle and trend in this modern era, but you must also be careful and pay attention to it. These include things that can later be called forms of Breach of contract. Default in online sales and purchase agreements has many forms and sometimes we experience it but are still not aware that this thing/event can be called an act of Breach of contract. For example: late payment, not making payment, sending goods but not according to what was agreed, sending goods but late, which will give rise to certain legal consequences.